2021
DOI: 10.1002/hep.32140
|View full text |Cite
|
Sign up to set email alerts
|

Ductular reaction promotes intrahepatic angiogenesis through Slit2–Roundabout 1 signaling

Abstract: Background and Aims: Ductular reaction (DR) expands in chronic liver diseases and correlates with disease severity. Besides its potential role in liver regeneration, DR plays a role in the wound-healing response of the liver, promoting periductular fibrosis and inflammatory cell recruitment. However, there is no information regarding its role in intrahepatic angiogenesis. In the current study we investigated the potential contribution of DR cells to hepatic vascular remodeling during chronic liver disease. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Several studies have shown that ROBO1 has important functions in angiogenesis. The activation of ROBO1 in vascular endothelial cells promoted angiogenesis ( 29 ). Furthermore, in human renal glomerular endothelial cells, the activation of SLIT2/ROBO1 signaling may contribute to angiogenesis through the PI3K/Akt/VEGF pathway ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that ROBO1 has important functions in angiogenesis. The activation of ROBO1 in vascular endothelial cells promoted angiogenesis ( 29 ). Furthermore, in human renal glomerular endothelial cells, the activation of SLIT2/ROBO1 signaling may contribute to angiogenesis through the PI3K/Akt/VEGF pathway ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 C). The atypical cells exhibited severe dysplasia, with an increased nuclear-cytoplasmic ratio and enlarged nuclei with hyperploidization 16 , 17 accompanied by fat deposition, ductular reaction 18 and fibrosis in zone 3 (the centrilobular region), as evaluated using Masson’s trichrome staining (blue staining, Fig. 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Slit2, known as a profibrotic and proangiogenic factor in the liver (29)(30)(31)(32) Animals, all males, were housed in a temperaturecontrolled, specific pathogen-free environment, on a 12-hour light-dark cycle, with free access to chow and water. Abcb4 -/mice and their wildtype Abcb4 +/+ littermates were bred, using Abcb4 +/heterozygous mice on an FVB/N genetic background (FVB.129P2-Abcb4tm1Bor/J) provided by Sanofi R&D (Chilly-Mazarin, France).…”
Section: Discussionmentioning
confidence: 99%
“…Slit2, known as a profibrotic and proangiogenic factor in the liver (29)(30)(31)(32), is a prototypical gene of PMSC/PMSC-MF signature. From the present data, we may postulate that following liver injury, SLIT2, produced by proliferating PMSCs/PMSC-MFs, promotes the formation of new vessels and the survival of HSC-MFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation